2022
DOI: 10.1002/aenm.202103820
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich‐Shell Structured CoMn2O4/C Hollow Nanospheres for Performance‐Enhanced Sodium‐Ion Hybrid Supercapacitor

Abstract: With the rapid depletion of petroleum and coal resources, the utilization of clean and sustainable energy (e.g., solar, hydropower, wind, and geothermal energy) has become particularly important. However, solar and wind energy have many intrinsic drawbacks, such as intermittence and instability, limiting their direct use. Therefore, it is urgent to develop high-performance electrochemical energy storage (EES) system to realize energy transfer. [1] Also, both electric vehicles and portable electronic devices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(41 citation statements)
references
References 68 publications
0
36
0
Order By: Relevance
“…1b, the diffraction peaks were consistent with Ni 4 OHF 7 (PDF#28-0697), indicating the successful synthesis of F–Ni–O 2 –R 2 . The envelope peak at 23° was attributed to the presence of amorphous carbon, 41 confirming the successful occurrence of organic ligand mechanisms. Further structural analysis by XRD demonstrated that F–Ni–O 2 –R 2 belongs to the hexagonal P 3̄ m 1(164) space group.…”
Section: Resultsmentioning
confidence: 66%
“…1b, the diffraction peaks were consistent with Ni 4 OHF 7 (PDF#28-0697), indicating the successful synthesis of F–Ni–O 2 –R 2 . The envelope peak at 23° was attributed to the presence of amorphous carbon, 41 confirming the successful occurrence of organic ligand mechanisms. Further structural analysis by XRD demonstrated that F–Ni–O 2 –R 2 belongs to the hexagonal P 3̄ m 1(164) space group.…”
Section: Resultsmentioning
confidence: 66%
“…While in the C 1s (Fig. 2f) high-resolution spectrum, the bonds of C-C/C=C, C-N, C-O, and C=O coexist, which probably originate from the pyridine and residual groups on the surface of rGO 46,47 .…”
Section: Resultsmentioning
confidence: 99%
“…In this case, hybrid supercapacitors commonly utilize a carbon-based material as one electrode by the physical sorption of ions and a batterytype electrode as the counter electrode via electrochemical conversation, which can release an admirable energy density without compromising the power delivery. Currently available battery-type materials are mainly based on transition metal oxides, [4,5] phosphides, [6,7] sulfides, [8,9] and hydroxides, [10,11] which are usually superior in specific capacity due to their multi-valence redox abilities, thereby sparking tremendous attention. 2D nickel-cobalt layered double hydroxides (2D NiCo-LDH), which possess an inverse spinel structure with Co 3+ , distribute on both octahedral and tetrahedral sites and Ni 2+ in octahedral sites, always feature high theoretical capacity (>3000 F g −1 ) and excellent reversibility, showcasing promising application prospects in energy storage and conversion field, especially in supercapacitor.…”
Section: Introductionmentioning
confidence: 99%